DIGITALISASI PRODUK KERAJINAN GOLOK GALONGGONG KABUPATEN TASIKMALAYA - Ramadhani, Indi; Mufreni, Alfin Nurfahmi; Rinandiyana, Lucky Radi; Bintari, Vivi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Galonggong Golok is a product produced by the community or family (home industry) in Galonggong village, Cilangkap Village. The function of the Galonggong machete, apart from being a tool and tool for daily needs, also has very high artistic value, especially when seen on the handle or in Sundanese perah, so many buyers use the Galonggong machete as a display or decorative object (Anugrah, 2012). Even though it has quite high potential, this does not mean that machete producers in Galonggong Village are free from problems. In particular, the impact of the COVID-19 pandemic has hit the business sector which has been one of the SME icons in Tasikmalaya Regency. Regarding efforts to survive amidst the shocks of the COVID-19 pandemic, several craftsmen have started to take advantage of online sales, but it is still not optimal. One of the problems faced by machete craftsmen is the lack of skills related to online marketing, especially how to make products that look attractive. As a result of meetings and discussions with partners, it was agreed that the main problem/challenge currently is that online marketing is not yet optimal due to the lack of skills related to this, especially how to make products look attractive or eye catching when marketed online, and partners do not yet have a special website for their business. Training activities are implemented through the delivery of information in the form of lectures and discussions regarding the significance of skills related to taking photos and videos, with the aim of making products more attractive when marketed online. This will allow partners to focus on the specific aspects that make each machete unique when taking product photos. Apart from that, partners also take advantage of special websites that have been provided to expand product marketing reach.